Comparison of oxygen uptake kinetics during severe-intensity laboratory and field cycling - Prinz, B.; Haselsberger, K.; Tschan, H.; Nimmerichter, A. (International Journal of Sports Medicine, 2019)
The O2-kinetic response to constant work rate exercise provides an insight into the adjustment of systemic oxygen transport and muscle metabolism. Whether O2-kinetics measured in laboratory conditions reflect O2-kinetics in field conditions has not yet been analysed. The aim of this study was to compare O2-kinetics between field and laboratory conditions. Thirteen competitive male cyclists (mean±SD age 23.3±4.1 years; VO2peak 68.2±4.7?mL.min-1.kg-1) completed two 6-min severe-intensity trials at 60 and 90 rev.min-1 in both conditions. Power output was measured with an SRM power meter and VO2 was measured with a portable gas analyser. The time constant (t), the time delay (TD) and the amplitude (Amp) were resolved by least square regression, and the VO2 slow component (SC) was calculated as the difference between the end-exercise VO2 and Amp. To determine differences between the trials, a repeated-measure ANOVA was conducted. The Amp and end-exercise VO2 were significantly higher during field cycling whereas the SC were significantly higher during laboratory cycling (all at p<0.001). No significant differences were found for t (p=0.24). Laboratory measures tend to underestimate the oxygen demand in field cycling. A higher cadence leads to greater oxygen demand in laboratory and field cycling.